2013
DOI: 10.1902/jop.2013.1340013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of periodontal disease on diabetes: systematic review of epidemiologic observational evidence

Abstract: RJ. Effect of periodontal disease on diabetes: systematic review of epidemiologic observational evidence. AbstractBackground: Periodontal disease and diabetes mellitus are common, chronic diseases worldwide. Epidemiologic and biologic evidence suggest periodontal disease may affect diabetes. Objective: To systematically review non-experimental, epidemiologic evidence for effects of periodontal disease on diabetes control, complications and incidence. Data sources: Electronic bibliographic databases, supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
148
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 332 publications
(155 citation statements)
references
References 42 publications
1
148
0
6
Order By: Relevance
“…For example, systemic inflammation precedes type-2 diabetes, 64,65 and emerging evidence associates severe periodontitis with incident diabetes. 66 Periodontitis is also a recognised independent risk factor for diabetes complications (e.g. cardio-renal complications) 66 in a dose-dependent manner, and further associates with elevated HbA1c and low-density lipoprotein cholesterol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, systemic inflammation precedes type-2 diabetes, 64,65 and emerging evidence associates severe periodontitis with incident diabetes. 66 Periodontitis is also a recognised independent risk factor for diabetes complications (e.g. cardio-renal complications) 66 in a dose-dependent manner, and further associates with elevated HbA1c and low-density lipoprotein cholesterol concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Among those, periodontal diseases are complex polymicrobial inflammatory diseases associated with dysbiosis of the dental biofilm that induces a long-lasting chronic inflammation of the periodontal supporting tissues, leading to alveolar bone destruction, and eventual tooth loss [6]. Over the years, strong evidence has accumulated to indicate that the pathogenic microbiota and the chronic inflammation established in periodontitis contribute to the onset and/or progression of several systemic inflammatory diseases such as cardiovascular diseases [7,8], diabetes [9], obesity [10], metabolic syndrome [11], respiratory disease [12], cancer [13], chronic kidney disease (CKD) [14] and rheumatoid arthritis (RA) [15]. Most research on the periodontitis-systemic disease relationship, however, has not determined causality, and the link between these diseases are bi-directional associations [16].…”
Section: Introductionmentioning
confidence: 99%
“…Further, there is evidence for direct links between oral health and general health. Systematic reviews concluded that poor oral hygiene and periodontal disease are risk factors for pneumonia, and possibly also for chronic obstructive pulmonary disease (Azarpazhooh and Leake 2006;Sjögren et al 2008), and that periodontal disease adversely affects diabetes outcomes (Borgnakke et al 2013). …”
Section: Introductionmentioning
confidence: 99%